2013
DOI: 10.3329/cardio.v6i1.16111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Blood Glucose Levels on Contrast Induced Nephropathy after Percutaneous Coronary Intervention in Patients not known to be Diabetic with Acute Coronary Syndrome.

Abstract: Background: Contrast-Induced Nephropathy (CIN) is an iatrogenic disorder, resulting from exposure to contrast media. The association between pre-procedural blood glucose levels and CI-AKI risk (regardless of pre-existing diabetes) is unknown. The present study was conducted to evaluate the incidence of CI-AKI in patients with admission hyperglycemia in non-diabetic ACS patients. Methods: This is Prospective, observational study done in the department of Cardiology, National Institute of Cardiovascular Diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Low SYNTAX score (d"22) was 16% and 56% in group I and II respectively indicates that patients of non-O blood group having less severe disease in comparison to O blood group patients. Similar results were observed in intermediate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and high (>32) SYNTAX score in group-I and group-II respectively.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Low SYNTAX score (d"22) was 16% and 56% in group I and II respectively indicates that patients of non-O blood group having less severe disease in comparison to O blood group patients. Similar results were observed in intermediate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and high (>32) SYNTAX score in group-I and group-II respectively.…”
Section: Discussionsupporting
confidence: 83%
“…According to Akhand et al 22 most prevalent risk factors were smoking (60%) and dyslipidemia (60%) among the patients of CAD. Islam & Majumder (2013) reported high prevalence of hypertension (20% in adult and 40-65% in elderly) in Bangladeshi population that contributes to CAD 25 . However, a study in USA Mukherjee et al 2005, these findings are different, where 30.5% was diabetic, 66.8% hypertensive, 60.6% dyslipidemic, 21.3% smoker.…”
Section: Hypothesismentioning
confidence: 99%
“…Random glucose testing is an optimal option in this situation. In clinical trials, researchers discovered that high random blood glucose significantly increased the risk of PC-AKI after PCI in patients with acute coronary syndrome who did not have diabetes ( 8 ). Previous study including 13,3792 non-diabetes patients concluded that an increased random glucose value is a risk factor for diabetes ( 27 ) and could predict acceptable overall glycemic control in non-insulin-dependent diabetic patients ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Investigating some novel and potentially modifiable predictors may help to minimize PC-AKI incidence. Recent studies found non-diabetic patients with elevated pre-procedural random glucose have a higher risk of PC-AKI ( 7 , 8 ). Both fasting glucose and random glucose can predict in-hospital events in STEMI patients, but random glucose is more convenient in real-time and easier to obtain ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigating some novel and potentially modifiable predictors may help to minimize PC-AKI incidence. Recent studies found non-diabetic patients with elevated pre-procedural random glucose have a higher risk of PC-AKI (7,8). Both fasting glucose and random glucose can predict inhospital events in STEMI patients, but random glucose is more convenient in real-time and easier to obtain (9).…”
Section: Introductionmentioning
confidence: 99%